2014
DOI: 10.1002/bdm.1825
|View full text |Cite
|
Sign up to set email alerts
|

Advice from Experience: Communicating Incomplete Information Incompletely

Abstract: People utilize advice often with limited knowledge of their advisers' expertise. We examine the effects of learning mode on giving and receiving advice in two separate but linked studies. Advisers learned about a choice between two lotteries from either description or experience before writing advice. The decision makers only read this advice before choosing between the options. Advisers who learned from description provided better summarized information more confidently and were ultimately preferred by the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…As such, relational aspects, such as mutual trust and acknowledgment of the other individuals’ competencies, play a major role in the advice giving and advice taking processes. Psychology research, for instance, has shown that decision makers who are knowledgeable about the advisor’s own learning techniques surprisingly discount the advice to a higher degree (Benjamin & Budescu, 2015), whereas disclosure of conflicting interests by the advisor counterintuitively increases decision makers’ advice taking (Sah et al, 2013), as decision makers perceive high social pressure for compliance in such cases.…”
Section: Discussion Opportunities For Future Research and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, relational aspects, such as mutual trust and acknowledgment of the other individuals’ competencies, play a major role in the advice giving and advice taking processes. Psychology research, for instance, has shown that decision makers who are knowledgeable about the advisor’s own learning techniques surprisingly discount the advice to a higher degree (Benjamin & Budescu, 2015), whereas disclosure of conflicting interests by the advisor counterintuitively increases decision makers’ advice taking (Sah et al, 2013), as decision makers perceive high social pressure for compliance in such cases.…”
Section: Discussion Opportunities For Future Research and Conclusionmentioning
confidence: 99%
“…Future research endeavors could build on insights on relationship conflicts, from research on the family business (Kellermanns & Eddleston, 2006), family therapy (Cole & Johnson, 2012), and individual psychology (Gino et al, 2012), to shed light on the noneconomic consequences of the advice taking process. The construct of disclosure of interests from psychology (Benjamin & Budescu, 2015; Sah et al, 2013) could help provide a more profound understanding of how advisors’ disclosure of their own interest increases advice taking. Such findings might be combined with, for example, stewardship theory (e.g., Gordini, 2012; Hiebl, 2013) to further explain how advisors on a long-term basis serve family firms to their best.…”
Section: Discussion Opportunities For Future Research and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous research has examined some factors that influence perceptions of advisor expertise (Feng & MacGeorge, 2010; MacGeorge et al, 2013), less is known about how advisors influence recipients’ perceptions of their expertise through their communication and the effects of those efforts on advice outcomes. Prior studies indicate that advice recipients are responsive to variation in advice message features that index the value of the advice and the advisor’s regard for the recipient (e.g., Benjamin & Budescu, 2014; Feng & Burleson, 2008). Our results suggest that the value of experience claims in supportive communication may depend heavily on the problem context.…”
Section: Discussionmentioning
confidence: 99%
“…Research engaging the judge advisor system suggests that perceived advisor confidence can influence advice implementation by serving as a proxy for advisor expertise (Sah et al, 2013; Sniezek & Van Swol, 2001); however, this line of research does not illuminate the messages advisors might themselves use to influence confidence ratings. Several studies indicate that recipients respond positively to message elements that signal the utility of advice, including recommendation clarity (Benjamin & Budescu, 2014) and arguments that support the advised action (Feng & Burleson, 2008). Correspondingly, advisors might influence perceptions of their expertise by claiming problem-relevant experience (MacGeorge et al, 2008).…”
mentioning
confidence: 99%